Cluster TIC et dynamiques urbaines à Bangalore : des logiques antagonistes destructrices de compétitivité ? - Alexandre Grondeau (Netcom)
The present article aims at setting out the conditions of the success and the location of an ICT cluster in Bangalore, through the urban and social impact triggered by such location. The incredible economic success of a cluster generates an urban divide and a transport saturation which metropolis’ governments do not succeed to stamp out. Also the purpose of this article will be to question both economical and urban developments logics, by pointing out the antagonism existing between them, which could turn out to be a competition restraint.